Infusing Mindset through Mathematical Problem Solving and Collaboration: Studying the Impact of a Short College Intervention - Jo Boaler; Kyalamboka Brown; Tanya LaMar; Miriam Leshin; Megan Selbach-Allen (MDPI AG, 2022)
After experiencing years of procedural teaching in K-12 mathematics classrooms, many students arrive at college with ideas about, and approaches towards, mathematics that are not helpful to their learning. Students' prior experiences and misconceptions can then negatively impact their experiences in university STEM courses. This paper describes a short course in the "big ideas" of calculus, that offered students an approach of problem-based learning, combined with mindset messages, otherwise known as a "mathematical mindset approach". The mixed-method study considered how a 'mathematical mindset' teaching intervention impacted the learning, achievement, and beliefs of incoming college students, finding that the intervention significantly changed students' ideas about mathematics, their own potential, and the value of collaboration. At the end of the course students also significantly improved their achievement on assessments of problem solving and collaboration. Importantly the course allowed students to believe in their own potential and to approach mathematics with a growth mindset, suggesting a role for such courses in students' mathematics pathways.